Effectiveness and safety evaluation of thrice weekly double strength vs daily single strength trimethoprim-sulfamethoxazole for prophylaxis of pneumocystis jirovecii pneumonia after kidney transplantation: a two year prospective cohort study - Hui Yang; Lizhen Pang; Xiaopeng Hu; Wei Wang; Bifang Xu; Xiaodong Zhang; Lihong Liu (Frontiers Media S.A., 2021)
Purpose: It is hard for clinicians to choose the best regimen for pneumocystis jirovecii pneumonia (PJP) prophylaxis. The aim is to evaluate the effectiveness and safety of thrice weekly double strength (TWDS) vs daily single strength (DSS) trimethoprim-sulfamethoxazole (TMP-SMX) for prophylaxis of PJP after kidney transplantation. Methods: Adult renal transplant recipients (RTRs) who were transplanted between January 1, 2015 and July 1, 2018 were evaluated. A total of 189 RTRs were prescribed PJP prophylactic regimen during the study period (TWDS group: n=98; DSS group: n=91). Results: Morbidity due to PJP infection was significantly higher in TWDS group as compared with DSS group (8.60% vs 1.14%, p= 0.021). There was a significant trend toward higher prevalence of confirmed PJP (log‐rank=0.021) in TWDS group. The use of DDS TMP-SMX for prophylaxis after kidney transplantation was associated with a 79% reduction in the incidence of PJP comparing the prophylactic regimen of TWDS. There was no significant difference between the two groups in the overall rate of premature TMP-SMX discontinuation and laboratory indexes. Conclusion: Six months of DSS TMP-SMX prophylaxis was more effective than TWDS TMP-SMX regimen with the same safety profile.